The Perceptions and Coping Style of Disaster Victims: A Case Study of Affected People from Earthquake in Phan District, Chiangrai - Srichai , Pongsook; Netsuwan , Paphawadee (Ratchaphruek Journal, 2021)
This study aimed to investigate the level of the perceptions, the coping style, and the factors influencing the coping style of people who affected by the earthquake event. Population were 122,644 people who are domiciled and residing in Phan district of Chiang rai. The sample were 354 people who experienced in an earthquake in May 2014 by multi-stage sample sampling from 6 sub-districts of Phan district. The research instrument was a questionnaire consisted of two parts including part 1: personal factors and part 2: the six points summated rating scale questionnaire in the perceptions and the coping style. The data were analyzed by frequency, percentage, average, standard deviation, pearson product moment correlation coefficient, and multiple regression. The results were that the total average of the perceived level and the coping style was at a high level. Age, income, cognitive toward the earthquakes, thoughts and feelings toward the earthquakes were associated with coping styles. The large effect size were cognitive toward the earthquakes, thoughts and feelings toward the earthquakes and age respectively. All these variables could predict coping style at 61% (R2=0.610). Raw score prediction equation was Y’ = 0.878 + 0.714 (cognitive toward the earthquakes) +0.145 (thoughts and feelings toward the earthquakes) - 0.13 (age).